2021
DOI: 10.1155/2021/6650333
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Associated Factors of Human Immunodeficiency Virus, Treponema pallidum, Hepatitis B Virus, and Hepatitis C Virus among Female Sex Workers in Dessie City, Northeast Ethiopia

Abstract: Introduction. Sexually transmitted infections (STIs) are prevalent in Ethiopia and elsewhere among different population groups particularly among female sex workers (FSWs). Because of their work and their behavior, FSWs are at high risk to acquire STIs. The aim of the study was to assess the seroprevalence and associated factors of HIV, HBV, HCV, and T. pallidum among FSWs in Dessie City, Northeast Ethiopia. Methods. This cross-sectional study was conducted in Dessie City, Amhara Region, Northeastern Ethiopia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 45 publications
5
27
7
Order By: Relevance
“…But, this finding was not statistically significant ( P >0.05), which is inconsistent with a study conducted in Nigeria. 28 On the other hand, similar findings to the current study were reported from Dessie, Ethiopia 13 and Burkina Faso. 8 The possible reasons may be the early onset of sexual intercourse, which represents an increased risk for sexually transmitted infections.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But, this finding was not statistically significant ( P >0.05), which is inconsistent with a study conducted in Nigeria. 28 On the other hand, similar findings to the current study were reported from Dessie, Ethiopia 13 and Burkina Faso. 8 The possible reasons may be the early onset of sexual intercourse, which represents an increased risk for sexually transmitted infections.…”
Section: Discussionsupporting
confidence: 91%
“… 10 From limited studies in Ethiopia, the highest prevalences were reported from Gondar (28.9%), 11 Mekelle (6%), 12 and Dessie (13.1%). 13 In other developed countries such as Brazil, 14 China, 15 Thailand, 16 and India 17 the prevalence of HBV among Female sex workers (FSWs) was 23.6%, 10.7%, 11.4%, and 3.6%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There is much variation in the prevalence HBV infection across countries, including those which have a lower prevalence than ours like Mexico 0.2% (34), Iran 1.1% (35), Greece 1.3% (36), Brazil 0.7% (37), those with similar prevalence to ours like Rwanda 2.5% (38), and countries in SSA having much higher prevalence than ours like Nigeria 17.1% (39), Kenya, 13.3% (40), and Ghana 15.0% (41). Similarly, isolated and limited studies on HBV conducted in different cities/towns in Ethiopia at various times reported varying prevalence by site and year of study - Dessie 13.1% (11), Hawassa 9.2% (14), Gonder 28.9% (15), and Mekelle 6% (16). This variation could largely be explained by the differences in sociodemographic characteristics of study populations, study settings, sample size, and sampling methods focusing on high-risk population groups.…”
Section: Discussionmentioning
confidence: 98%
“…There are limited data from isolated studies showing the prevalence of HBV in Ethiopia - Hawassa 9.2% (14), Gonder 28.9% (15), Mekelle 6% (16), Dessie 13.1% (11), and northwest Ethiopia (11.9%) (17). FSW have been identified as a population group with the highest risk for STI, including HBV and HCV, and should perceive priority in the national HIV/AIDS program (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation